2007
DOI: 10.1518/001872007779598127
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Wrist Posture Based on Carpal Tunnel Pressure Thresholds

Abstract: The method presented can provide wrist posture guidelines for the design of tools and hand-intensive tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 40 publications
4
67
3
3
Order By: Relevance
“…Keir, Bach, and Rempel (1999) found similar values of wrist extension when using different mice and an increase in carpal tunnel pressure during mouse tasks. Overall, carpal tunnel pressure increases with extension, and prolonged extension greater than 40° can create pressures above 30 mmHg (Keir, Bach, Hudes, & Rempel, 2007). In the present study, wrist extension was found to be similar with the alternative mouse and the standard mouse in the trained group but increased with no training.…”
Section: Discussionsupporting
confidence: 54%
“…Keir, Bach, and Rempel (1999) found similar values of wrist extension when using different mice and an increase in carpal tunnel pressure during mouse tasks. Overall, carpal tunnel pressure increases with extension, and prolonged extension greater than 40° can create pressures above 30 mmHg (Keir, Bach, Hudes, & Rempel, 2007). In the present study, wrist extension was found to be similar with the alternative mouse and the standard mouse in the trained group but increased with no training.…”
Section: Discussionsupporting
confidence: 54%
“…It has been demonstrated in past studies that wrist flexion and extension lead to increased carpal tunnel pressure, a proposed mechanism leading to CTS 38. Although our computer-assisted posture analysis method represents an improvement over earlier direct observation methods,39 there was still relatively low interobserver agreement (κ=0.42–0.78) and more missed ratings of wrist postures compared with larger joint movements such as arm elevation in our study (κ=0.72–0.84).…”
Section: Discussionmentioning
confidence: 99%
“…In maximaler Handgelenksextension und -flexion werden maximale Druckanstiege erreicht. Die Extension könnte sogar ein stärkerer Faktor der Druckerhöhung im Karpaltunnel sein, wie Untersuchungen von Weiss et al[109] und Keir et al[60] zeigen. In der klinischen Untersuchung hat sich der Phalen-Test als Test maximaler Flexion als hinreichend für die Diagnostik erwiesen und ist damit als Standard der Untersuchung etabliert.…”
unclassified